Impacts of integrating practical classes into the teaching of chemistry in senior secondary schools - Ojelade, Iyabode Adenike (Advances in Social Sciences Research Journal, 2015)
This study was designed to investigate the impacts of integration of practical into the teaching of chemistry in some selected senior secondary schools in Abuja Municipal Area Council. A survey research design was adopted for the study while simple random sampling technique was used to select a total of 200 respondents from six schools in Abuja Municipal Area Council of the Federal Capital Territory that constituted the sample size for the study. The main instrument used for the study was questionnaire and the data collected were analysed using frequency counts and percentage. The findings of the study revealed that practical helps for better assimilation of chemistry and lack of equipped school laboratory inhibits practical chemistry in our schools. Based on these, it is recommended that teachers should utilize experimental methods in teaching science subjects and government should provide teaching materials, laboratory equipment, and standard curriculum so as to enhance the teaching and learning of chemistry in our secondary schools.